Optimasi Kandungan Gizi Dan Biaya Bahan Pangan Pada Makanan Sehat Untuk Penderita Kolesterol Tinggi (Dyslipidemia) Menggunakan Algoritma Evolution Strategies - Rayindita Siwie Mazayantri; Randy Cahya Wihandika; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Nowadays there are changes that occurring in our community, especially in technology department, that causes changes in lifestyle which results in imbalanced nutrition. Something like this could lead the body to catch symptoms of dyslipidemia, which is a disease wherein the level of blood lipids is high and hence higher possibilities of causing many more dangerous diseases. To reduce the level of cholesterol, it is highly recommended to examine the food contents and ingredients. For some people, it may not be easy to manage what ingredients they should consume due to lack of knowledge in that aspect, so to solve the problem we could apply Evaluation Strategies method, which has initialization process of chromosome representation as real-vector. In this study, the ES cycle that we apply is (Âµ+Î») that only requires mutation without recombination. The next process is fitness calculation, and evaluation, and then do the selection process. From the testing of parameters, we can conclude that the system can yield the most optimized results when the size of population is set to 120, offspring is set to 160, and generation is set to 40. A solution that the system can come up with compared to the experts' recommendation shows that the solution this system gave is more optimal, with 2.2825 as a fitness value, higher than the fitness that we get from experts' recommendation which only 0.4003, so the system can provide recommendations for cheap ingredients while reckoning the needs for nutrients intake of the patients.